PENGARUH PENGGUNAAN VIDEO PEMBELAJARAN INTERAKTIF MODEL DISCOVERY LEARNING PADA KEMAMPUAN MENULIS KARYA ILMIAH FASE F SMAN 11 MUARO JAMBI - Sebi Aprial, Pernando; Hary Soedarto Harjono; Siti Enik Mukhoiyaroh Bambang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the effect of interactive learning videos based on the Discovery Learning model on students’ scientific writing skills in Phase F at SMAN 11 Muaro Jambi. This research employed a quantitative pre-experimental method using a one-group pretest-posttest design. The sample consisted of one experimental class selected purposively. Data were collected through pretest and posttest writing assessments evaluated using a structured rubric. Statistical analysis included normality testing and hypothesis testing using t-test. The results showed a significant improvement in students’ scientific writing ability after the implementation of interactive video-based Discovery Learning. The findings indicate that the integration of interactive video media with Discovery Learning stages effectively enhances students’ understanding of scientific writing structure, argument development, and systematic composition. Therefore, interactive learning videos can serve as an innovative instructional strategy to improve scientific writing competence in senior high school students.